Nevus lipomatosus cutaneous superficialis. Report of a case. - Buzluk, S.A.; Erkin, G.; Boztepe, G.; Özkaya, O. (European Journal of Pediatric Dermatology, 2003)
Nevus lipomatosus cutaneous superficialis is a rare nevoid anomaly characterized by the presence of mature ectopic fat tissue in the dermis. It is classified into two clinical types as follows: multiple (classic) and solitary type. We report a case of nevus lipomatosus cutaneous superficialis with multiple lesions in a 12-year-old girl, review the recent literature and discuss the differential diagnosis.